A novel homozygous PTH1R variant identified through whole-exome sequencing further expands the clinical spectrum of primary failure of tooth eruption in a consanguineous Saudi family. (July 2016) - Jelani, Musharraf; Kang, Changsoo; Mohamoud, Hussein Sheikh Ali; Al-Rehaili, Rayan; Almramhi, Mona Mohammad; Serafi, Rehab; Yang, Huanming; Al-Aama, Jumana Yousuf; Naeem, Muhammad; Alkhiary, Yaser Mohammad
Highlights: PFE is mainly associated with heterozygous mutations in PTH1R gene. A PFE family with autosomal recessive inheritance underwent whole-exome sequencing. A novel homozygous variant of PTH1R was identified as causative of PFE. It is the first report of homozygous PTH1R mutation causing PFE in a Saudi family. Abstract: Objectives: The present study aimed to identify the genetic cause of non-syndromic primary failure of tooth eruption in a five-generation consanguineous Saudi family using whole-exome sequencing (WES) analysis. Design: The family pedigree and phenotype were obtained from patient medical records. WES of all four affected family members was performed using the 51Mb SureSelect V4 library kit and then sequenced using the Illumina HiSeq2000 sequencing system. Sequence alignment, variant calling, and the annotation of single nucleotide polymorphisms and indels were performed using standard bioinformatics pipelines. The genotype of candidate variants was confirmed in all available family members by Sanger sequencing. Results: Pedigree analysis suggested that the inheritance was autosomal recessive. WES of all affected individuals identified a novel homozygous variant in exon 8 of the parathyroid hormone 1 receptor gene ( PTH1R ) (NM_000316 : c.611T>A: p.Val204Glu). Conclusion: To the best of our knowledge, this is the first report of primary failure of eruption caused by a homozygous mutation in PTH1R . Our findings prove the application of WES as an efficient molecular diagnostics tool for this rare phenotype and further broaden the clinical spectrum of PTH1R pathogenicity.